2011
DOI: 10.4269/ajtmh.2011.11-0116
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Pathogens Associated with Childhood Diarrhea in Tripoli-Libya

Abstract: Abstract. Stool samples from children < 5 years of age with diarrhea ( N = 239) were examined for enteric pathogens using a combination of culture, enzyme-immunoassay, and polymerase chain reaction methods. Pathogens were detected in 122 (51%) stool samples; single pathogens were detected in 37.2% and co-pathogens in 13.8% of samples. Norovirus, rotavirus, and diarrheagenic Escherichia coli (DEC) were the most frequently detected pathogens (15.5%, 13.4%, and 11.2%, respectively); Salmonella , adenovirus, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 38 publications
8
35
1
Order By: Relevance
“…Similarly, Rahouma and others 26 reported that EAEC (5.4%) is the main pathotype of DEC in diarrheic Libyan children in Tripoli. Several studies from developing countries reported high detection rates (20-38%), whereas other investigators reported low detection rates (5 -6%) for EAEC from children with diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Rahouma and others 26 reported that EAEC (5.4%) is the main pathotype of DEC in diarrheic Libyan children in Tripoli. Several studies from developing countries reported high detection rates (20-38%), whereas other investigators reported low detection rates (5 -6%) for EAEC from children with diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have found DEC among the leading enteric pathogens, in addition to rotavirus and norovirus, associated with childhood diarrhea in Tripoli, Libya, with the predominance of EAEC. 26 The aims of this work were to determine the frequency of DEC among children with diarrhea and from Zliten and Alkhomes city water sources; furthermore, the phylogenetic grouping and virulence-encoding Stool specimens from enrolled children were collected using wide-mouthed sterile plastic containers and transported immediately to the microbiology laboratory for analysis within two hours of collection.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of Aeromonas-associated gastroenteritis on a global basis varies dramatically in association with geographic and socioeconomic factors. In developing countries where sanitary conditions are substandard, the reported incidence of Aeromonas diarrhea can be high, ranging from approximately 4% to 22% (13)(14)(15)(16). In industrialized countries, regardless of patient population and sample size, Aeromonas-associated gastroenteritis has been reported at frequencies of 0% to 10% (17,18).…”
Section: Aeromonas Speciesmentioning
confidence: 99%
“…Eighty percent of these deaths are among children under two years of age. Predisposing factors such as malnutrition, low socioeconomic conditions, and poor hygiene are the major risk factors for such deaths in developing countries (3)(4)(5)(6)(7)(8). Among the bacteria responsible for diarrhea, Salmonella spp., Shigella spp., E. coli, Campylobacter spp., Vibrio cholerae, Aeromonas hydrophila, and Plesiomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…Among the bacteria responsible for diarrhea, Salmonella spp., Shigella spp., E. coli, Campylobacter spp., Vibrio cholerae, Aeromonas hydrophila, and Plesiomonas spp. are the most common agents of diarrhea (2,5,6). In spite of fluid and electrolyte replacement as a method of choice for the treatment of diarrheal diseases, antimicrobial therapy is recommended for suspected cases of Salmonella, Shigella and V. cholerae (7).…”
Section: Introductionmentioning
confidence: 99%